Implementasi Model Pembelajaran Talking Stick yang Dibantu Manipulatif Stinepo pada Operasi Pengurangan Bilangan Bulat di Kelas VII - Pitriana Tandililing; Mayor M.H. Manurung; Annisa Kurnia Sari (Journal of Research in Science and Mathematics Education, 2026)
Purpose: Teaching integer subtraction remains challenging because many students rely on procedural rules rather than conceptual understanding. This study aimed to investigate the implementation of the Talking Stick cooperative learning model assisted by Stinepo manipulatives and to describe students’ affective participation and learning outcomes in Grade 7 mathematics. Methodology: A descriptive mixed-methods classroom implementation design was conducted with 15 Grade 7 students at MTs Muhammadiyah Jayapura. Data were collected through classroom observation, learning documentation, group worksheets, affective assessment, and an individual written test, and were analyzed descriptively. The learning process integrated structured preparation, concept explanation, cooperative group discussion, concrete representation of integer subtraction using Stinepo, game-based questioning through the Talking Stick strategy, and individual assessment. Findings: The findings showed that the approach promoted active classroom participation, collaboration, responsibility, confidence, and conceptual engagement. Students achieved a total affective score of 202 out of 240, equivalent to an average converted score of 3.37, indicating a very good level of participation. The mean written test score was 76.33, and 12 of the 15 students (80%) achieved the school mastery criterion. Significance: The integration of cooperative learning and low-cost manipulatives enabled students to connect concrete representations with symbolic reasoning while increasing individual accountability during mathematical discussions. These findings suggest that combining the Talking Stick model with Stinepo manipulatives provides a practical and effective instructional strategy for improving conceptual understanding and classroom engagement in teaching integer subtraction, particularly in resource-limited mathematics classrooms.